Post war planning & Anglo-American divergence of attitudes on Siam. - Nik Anuar Nik Mahmud (Universiti Kebangsaan Malaysia, 1978)
The framers of Britain's policy considered Thailand to be important as far as the security and economic well-being of her territories in Southeast Asia were concerned, and this necessitated that British imposed certain post-war arrangements on Thailand. Nevertheless in formulating the arrangements the Foreign Office had to accommodate it with the Atlantic Charter and Cairo Declaration and the views put forth by the United States. The emerging role of the United States as a major post-war power had to be reckoned with by Britain especially because she depended economically and strategically on the United States not only for war efforts but also for post-war economic recovery. It had been the United States policy to bring the British policy in line with her interests and viewpoints. Although Britain agreed to pursue a similar course of action in certain aspects concerning South Asia, East Asia and the Pacific Region, she found it difficult to reconcile herself with the American viewpoints as far as Thailand was concerned. The divergent viewpoints of the countries with regard to Thailand affected the Anglo-Thai peace settlement negotiations.